Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.tips.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Is resistance useless? Multidrug resistance and collateral sensitivity

Abstract: When cancer cells develop resistance to chemotherapeutics, it is frequently conferred by the ATPdependent efflux pump P-glycoprotein (MDR1, P-gp, ABCB1). P-gp can efflux a wide range of cancer drugs; thus its expression confers cross-resistance, termed multidrug resistance (MDR), to a wide range of drugs. Strategies to overcome this resistance have been actively sought for over 30 years, yet no clinical solutions exist. A less understood aspect of MDR is the hypersensitivity of resistant cancer cells to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
194
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(201 citation statements)
references
References 105 publications
4
194
0
3
Order By: Relevance
“…In 3 different ABCB1-overexpressing cell-line systems, we previously demonstrated that the use of fludarabine decreases the resistance index more in the resistant sublines than in their parental ones. 15 The precise mechanism of this phenomenon, named collateral sensitivity, 16 by which multidrug-resistant cells become hypersensitive to a series of drugs that are not substrates of MDR proteins remains to be determined. Moreover, our induction course contained idarubicin, which usually is not included in the list of ABCG2 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In 3 different ABCB1-overexpressing cell-line systems, we previously demonstrated that the use of fludarabine decreases the resistance index more in the resistant sublines than in their parental ones. 15 The precise mechanism of this phenomenon, named collateral sensitivity, 16 by which multidrug-resistant cells become hypersensitive to a series of drugs that are not substrates of MDR proteins remains to be determined. Moreover, our induction course contained idarubicin, which usually is not included in the list of ABCG2 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that multidrug-resistant cells exhibit collateral sensitivity to selected compounds. However, in contrast to the isatin-β-thiosemicarbazones (1a-e), the selective toxicity of the newly investigated compounds (2c, 3a, 4c, 4b, 5b, 5a, 6a, 6b) was not influenced by the P-gp inhibitor Tariquidar (TQ), suggesting that the observed hypersensitivity of the MDR cells cannot be exclusively linked to the activity of P-gp, and should be rather explained by off-target effects linked to other specific resistance mechanisms or the genetic drift of the selected cells [39,71,72]. In a similar manner, enhanced toxicity of the N-(2-mercaptopropionyl)glycine tiopronin against a subset of (but not all investigated)…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Another example is the natural product Austocystin D, which possesses increased toxicity against some MDR cell lines as a result of increased activation by cytochrome P450 [75]. Increased sensitivity of MDR cells to the antimetabolite 2-deoxy-dglucose, the electron transport chain inhibitors rotenone and antimycin A [71,76,77] as well as certain P-gp-substrates [72,[78][79][80] were explained by the ATP depleting effect of the transporter. According to this model, increased glycolysis compensates for the higher energy demand created by the "futile cycling" of the transporter [79,81,82], but the oxidative stress associated with oxidative phosphorylation ultimately results in the selective apoptosis of MDR cells [83].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Multidrug resistance and DNA repair are of prime concern with DNA alkylating agents. 7,8 Intriguingly, BO-1090 was more effective in Taxol-and vincristine-resistant KB cell lines (Supporting Information Table 4), which exhibit the pg170/ MDR1 resistance phenotype, 14 than in parental KB cells. The resistance ratio (ratio of IC50 of resistant to parental cell) of BO-1090 was 0.93 for Taxol-resistant and 0.731 for vincristine-resistant cells, indicating that BO-1090 may bypass the MDR1 effect.…”
Section: Cancer Therapymentioning
confidence: 98%
“…5,6 Occurrence of resistance to DNA alkylating agents in cancer cells may be due to decreased uptake of the agent into cells, increased drug extrusion, drug inactivation in the cells due to chemical instability, or quick repair of DNA lesions. 7,8 Additionally, methylated adducts formed by drug treatment can be removed and repaired by O 6 -methylguanine-DNA methyltransferase (MGMT), which is responsible for drug resistance to temozolamide and BCNU. 7,9 Although toxicity and resistance are the major problems associated with alkylating agent chemotherapy, numerous alkylating agents remain the first line drugs to treat a variety of cancers.…”
mentioning
confidence: 99%